Anesthetic Considerations in Cardiac Patients Undergoing Neurosurgery - Bhatt, Rashmi; Khanna, Puneet (Journal of Neuroanaesthesiology and Critical Care, 2019)
Elective and emergency neurosurgical procedures pose considerable risk in patients with cardiac disease. As the incidence of cardiac disease has increased in the general population over the past few decades, it is imperative to familiarize oneself with the challenges posed and the recommended management guidelines. The eventual outcome is significantly altered by the nature and severity of the underlying cardiac condition, as is the anesthetic management. A well-optimized cardiac condition can reduce morbidity and mortality considerably, which, however, may not be possible in neurosurgical emergencies. This review aims to look at various pathophysiological implications of cardiac disease, against the background of anesthetic management of neurosurgery. The discussion includes assessment and stratification of risk, appropriate investigations indicated, and the plan of anesthetic management. Even though no specific guidelines have been formulated, the discussion is largely to derive from the guidelines for patients with cardiac disease undergoing noncardiac surgery.
Keywords: anesthetic considerations; cardiac disease; neurosurgery